Ligand Engineering of Co‐N4 Single‐Atom Catalysts for Highly‐Active and Stable Acidic Oxygen Evolution - Taeyoung Jeong; Kiwon Kim; Byung‐Hyun Kim; Sang‐Il Choi; Chang Hyuck Choi; Joonhee Kang; Myeongjin Kim (Advanced Science, 2025)
Abstract The development of stable and efficient single‐atom catalysts (SACs) for the oxygen evolution reaction (OER) in acidic media remains challenging. This work reports a novel NH3‐assisted pyrolysis strategy to synthesize Co‐N4 SACs with controlled nitrogen coordination environments on crumpled graphene supports. The pyrrolic N4‐coordinated Co sites demonstrate superior OER activity compared to their pyridinic counterparts, achieving an overpotential of 351 mV at 10 mA cm−2 in 0.5 m H2SO4. Combined density functional theory calculations and operando X‐ray absorption spectroscopy reveal that the pyrrolic coordination environment facilitates enhanced OH− adsorption and subsequent OER kinetics due to its unique electronic structure and geometric flexibility. A multi‐layered protective mechanism in the pyrrolic system enables exceptional stability during long‐term acidic OER operation, stemming from higher defect formation energy of Co sites and strategic distribution of sacrificial nitrogen species in the graphene network. These findings provide fundamental insights into designing stable single‐atom catalysts for challenging electrochemical applications.